Internal Communication and Inclusive Leadership in Relation to Employee Performance: a Case Study of a Seat Cover Manufacturer - Shafira Rahmahwati Kuswandi; Andika Putra Pratama (KOLONI, 2026)
Manufacturing remains one of the main pillars of Indonesia’s economy, yet its competitiveness now rests more on how firms manage communication, leadership, and day-to-day execution than on production scale alone. This study sets out to understand how internal communication and inclusive leadership are practiced in relation to employee performance at PT SSC, an export-oriented car seat cover manufacturer in West Java that met its sales target but did not turn that into steady daily output. The study uses a qualitative case study approach. Data were drawn from fourteen informants across four divisions through semi-structured interviews, observation, and internal records, and were then analysed thematically and triangulated. The findings show that communication routines, leadership roles, and worker capability already exist but are not joined up in daily work, which leaves uneven understanding, inconsistent inclusive leadership, and gaps in capability. The study proposes an integrated people-performance execution system built on three linked pillars, which may offer practical value for labor-intensive manufacturers facing similar problems.